Same map, different direction – Exploring new opportunities that dementia care mapping™ can offer to acute mental health admission wards for older people – Innovative practice. (February 2020) - Page, Sean; Davies-Abbott, Ian; Phillips, Mat
Dementia Care Mapping™ is widely acknowledged as the gold standard observational method that can support the introduction of person centred care into a variety of settings (http://www.bradford.ac.uk/health/dementia/dementia-care-mapping/ ). It encourages care staff to think about how the person with dementia is experiencing the care provided and the care setting. It has been shown to raise care staff awareness sufficiently to bring about improvements in care. In this paper, we describe a programme of work in North Wales that seeks to find innovative ways to use Dementia Care Mapping™, in acute mental health admission wards for people affected by dementia, and we set out some of those innovations.